Pelanggaran Wilayah Udara Indonesia Oleh Pesawat Asing Menurut Hukum Internasional - Tiwery, Zepty Fence; Hanafi, Irma Halima; Riry, Welly Angela (Balobe Law Journal, 2024)
Introductioan: Indonesian airspace violation committed by a foreign aircraft in the case of the forced landing of a Boeing 777 foreign cargo plane on January 14, 2019. The aircraft entered Indonesian airspace without permission or Flight Clearance (FC) so it had to be forcibly landed by the Indonesian Air Force at Hang Nadim International Airport, Batam, Riau Islands. Such violations are clearly contrary to applicable law.Purposes of the Research: Know the regulation of Indonesian airspace according to international law and how law enforcement in Indonesian airspace.Methods of the Research: Normative juridical which conducts research on law based on laws and regulations related to the problem under study. The research approach carried out is the concept approach, legislation approach and case approach.Results of the Research: The regulation of Indonesian airspace according to international law must use the provisions of international law such as the Chicago Convention of 1944 and Law No.1 of 2009, Government Regulation No.4 of 2018 and Law No.34 of 2004. Law enforcement in Indonesian airspace still experiences limitations and obstacles due to the fact that foreign aircraft can enter. Therefore, there are still many obstacles in surveillance and defense equipment because it does not have radar that has the ability to detect incoming foreign aircraft so that the TNI must coordinate first..